Aromaterapi Untuk Menurunkan Intensitas Nyeri Fraktur: Literature Review - Paskarina, Priskila (Universitas Tanjungpura, 2023)
Background: Fractures can cause pain resulting in damage to the bones andtendons, which is unpleasant, subjective, and is part of the result of breakingthe continuity of the bone. Fracture pain is an unpleasant sensation. There are2 fracture pain management, namely pharmacologically and nonpharmacologically. Pharmacologically using drugs and nonpharmacologicallyusing aromatherapy. Aromatherapy can be given in several ways, one of themost effective ways is inhalation. Aim: The aim of this study was to analyzethe journals related to the relationship between aromatherapy in reducingfracture pain. Method: Using a literature review. The research samplesanalyzed were 7 articles. Data collection tools are Research Gate, Pubmed,Google Schollar, and Proquest. Data analysis using PICO. Result: Seven outof fiveteen articles used in this literature review show significant influence theeffect aromatherapy on reducing pain intensity. Conclusion: The use ofaromatherapy can be given to patients who experience fracture pain becauseafter an analysis of several articles there is a relationship between one articleand another in reducing the intensity of fracture pain.Keywords : Aromatherapy, Fracture, Pain